KONSEP BRAND STORYTELLING, VALUE PERCEPTIONS DAN VISIT INTENTION PADA KAWASAN TUJUAN WISATA DI JAKARTA - Lily Anita, Tiurida; Sukma Lestari, Nurul (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p13, 2020)
This study aims to examine the effect of brand storytelling on value perceptions and its impact on Visit Intention on tourism destinations in Jakarta (Survey on YouTube Channel of Taman Mini Indonesia Indah). The survey was conducted on 100 subscribers of the YouTube Channel of TMII Official. With purposive sampling technique and Path analysis technique to analyze this study, the results show that 1) Brand storytelling has a significant effect of 0.680 or 68,0% on value perceptions; 2) Value perceptions significantly influence 0,477 or 47,7% to visit intention; 3) Brand storytelling directly affects significantly 0,438 or 43,8%, to Visit intention, while its influence indirectly equal to 0,324 or 32,4% through value perceptions, with total influence 0,762 or 76,2%. The findings in this study indicate that Brand storytelling is one of the effective strategies in forming value perceptions so that it can influence visit intention.